Development of Interactive Digital Teaching Materials Based on Problem Based Learning Cultural Diversity Materials in Social Sciences Learning - Haruna, Nana Harlina; Masri, Sulfiana (Cokroaminoto Journal of Primary Education, 2024)
Diverse open materials have not been developed by teachers for the learning process. This has an impact on students' low social studies learning outcomes. The aim of this research is to create problem-based digital teaching materials that teach cultural diversity in social studies learning for fourth grade students. This research is a type of development research that uses the ADDIE development model. A non-test in the form of a questionnaire sheet is used. In this research, the product was tested for feasibility by subject content experts, learning design experts, and learning media experts. Product usability tests were carried out on individual and small groups of students in class IV elementary school. The results of this research design produced digital teaching material products consisting of text, images, videos and interactive quizzes. Subject content experts tested the product with a percentage of 76.923 percent (good). Product feasibility testing by learning design experts obtained 92.5% (very good), learning media experts obtained 93.75% (very good), and individual trials obtained 85.25% (very good), and small group trials obtained 89.52% (very good). The results show that problem-based digital teaching materials that focus on learning cultural diversity material can be used for social studies learning for fourth grade elementary school students